Records of Convocation, XV, York, 1625-1861 - Bray, Gerald 1948- (The Boydell Press, 2024)
The convocation records of the Churches of England and Ireland are the principal source of our information about the administration of those churches from middle ages until modern times. They contain the minutes of clergy synods, the legislation passed by them, tax assessments imposed by the king on the clergy, and accounts of the great debates about religious reformation; they also include records of heresy trials in the fifteenth and sixteenth centuries, many of them connected with the spread of Lollardy. However, they have never before been edited or published in full, and their publication as a complete set of documents provides a valuable resource for scholarship. This volume covers the York records between 1625 and 1861. It includes a detailed account of the seventeenth century and a calendar of the later period, including lists of those who were summoned to attend the convocation. Of particular interest is the material relating to the revival of the convocation in the nineteenth century, which did not proceed as smoothly as it did in Canterbury. The volume also gives a complete list of the prolocutors in so far as they are known from the middle ages to the present day